2007
DOI: 10.1590/s0004-27302007000700018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de síndrome metabólica em estudo de base populacional, Vitória, ES - Brasil

Abstract: Prevalence of Metabolic Syndrome in Population-Based Study, Vitória, ES -Brazil. Metabolic Syndrome (MS) is a complex disorder including several factors predisposing to development of cardiovascular diseases and diabetes. Despite the importance of MS for the health system, the epidemiological characteristics of this condition in the Brazilian population are still scarce. The prevalence of MS as a function of gender, age and socioeconomic level was determined in a population-based study in Vitória, ES, Brazil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2
52

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 21 publications
8
54
2
52
Order By: Relevance
“…This result was observed in several other studies such as those conducted in the USA 23 and Chile 25 , as well as in Brazil, in Vitória-ES 27 , and Bahia 28 , possibly due to reduced physical activity and increased intake of large amounts of calories in these populations.…”
Section: Factors Associated With Metabolic Syndromesupporting
confidence: 72%
“…This result was observed in several other studies such as those conducted in the USA 23 and Chile 25 , as well as in Brazil, in Vitória-ES 27 , and Bahia 28 , possibly due to reduced physical activity and increased intake of large amounts of calories in these populations.…”
Section: Factors Associated With Metabolic Syndromesupporting
confidence: 72%
“…A study conducted in the semiarid region of Bahia State with 138 women found 18.2% of MS (NCEP-2001) among women under the age of 45 and 56.9% among those that were 45 years or older 22 . A study conducted in the city of Vitória, State of Espírito Santo, which evaluated 887 women, found prevalence of MS (NCEP-2001) of 33.6% in women aged 45 to 54 and 53.4% among those aged 55 to 64 23 . A study conducted in Seychelles found prevalence of 46% and 68% among women in the 45 to 54 and 55 to 64 age groups 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In the city of Vitoria, State of Espírito Santo, there was an inversion only in the first two components. The other ones followed the same order 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Excess fat, especially in the upper body, is associated with lipid profile changes, increased blood pressure and hyperinsulinemia, factors that increase the Cardiovascular Disease (CVD) risks [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, this prevalence was even higher in 2009/2010, affecting 35.5% of men and 35.8% of adult women [3][4][5]. Excess fat, especially in the upper body, is associated with lipid profile changes, increased blood pressure and hyperinsulinemia, factors that increase the Cardiovascular Disease (CVD) risks [6][7][8].…”
Section: Introductionmentioning
confidence: 99%